Ethical challenges during the COVID-19 pandemic: Perspectives of nursing students. (March 2022) - Palacios-Ceña, Domingo; Velarde-García, Juan Francisco; Espejo, Marta Mas; González-Hervías, Raquel; Álvarez-Embarba, Beatriz; Rodríguez-García, Marta; Oliva-Fernández, Oscar; González-Sanz, Pilar; Moro-López-Menchero, Paloma; Fernández-de-las-Peñas, César; Cachón-Pérez, Jose Miguel
Background: The first wave of the COVID-19 pandemic caused a shortage of qualified nurses in Spain. As a result, the government authorized the hiring of senior students. Objectives: To explore the ethical dilemmas and ethical conflicts experienced by final-year nursing students who worked during the first outbreak of the COVID-19 pandemic in Spain. Research design: A qualitative exploratory study was conducted using purposive sampling. Semi-structured interviews were carried out using a question guide. Interviews took place via a private video chat room platform. A thematic, inductive analysis was performed of the information gathered. Participants and research context: Eighteen nursing students were recruited from two universities of Madrid, aged between 18 and 65 years old, enrolled in the fourth year of nursing studies and who were hired under a relief contract for health professionals during the pandemic. Ethical considerations: The present study was carried out in accordance with the Declaration of Helsinki, and the study was approved by the Local Ethics Committee of Universidad Rey Juan Carlos. Results: Three specific themes emerged: (a) coping with patient triage, (b) difficulties in providing end-of-life care, and (c) coping with patient death. Nursing students participated in the process of patient selection for resource allocation and ICU bed occupancy. They were shown how to care for patients who were not admitted to the ICU, in their last moments and were faced with the difficulties of applying end-of-life care. Finally, the nursing students were confronted with the death of their patients, in overwhelming numbers and under adverse conditions. Conclusions: These findings can help shed light on the ethical dilemmas and ethical conflicts faced by novice nursing students, incorporated into the workforce during the COVID-19 pandemic. Moreover, it was described that students may normalize the death due to the exhaustion and overwhelmed routine.